Analisis Pengaruh Influencer Marketing, Brand Image, dan Kualitas Produk Terhadap Keputusan Pembelian Produk Glad2glow Perfect Cover Cushion Pada Aplikasi Tiktok Shop - Jauzaa Ronaa Nuur Aqiila; Ida Ayu Nuh Kartini (CV. Ulil Albab Corp, 2026)
The purpose of this study is to look into how Glad2Glow Perfect Cover Cushion purchase decisions among Generation Z TikTok Shop customers in Surabaya are influenced by Influencer Marketing, Brand Image, and Product Quality. Data were gathered from 101 purposively chosen respondents who had bought the goods through TikTok Shop using a quantitative survey method. The data were processed using validity, multiple regression analysis, t and F tests, coefficient of determination, and reliability tests, and tests of classical assumptions. The findings demonstrate that brand image, product quality, and influencer marketing all greatly affect consumers' decisions to buy. Although Brand Image and Product Quality have positive and substantial benefits, with Product Quality being the most important aspect, Influencer Marketing has a negative and significant influence. These findings indicate that although influencer promotions are important, Generation Z consumers place greater emphasis on product quality and brand perception when making purchasing decisions.